Upcycling eco-village in Perhentian Kecil island - Othman, Aida Haslinda; Yusof, Zeenat Begam (Kulliyyah of Architecture and Environmental Design, 2020)
Upcycling and recycling are among the components under solid waste management which needs to be carried out in order to make solid waste management successful in Malaysian marine park islands. Current issues at marine park islands are accumulation of solid waste in the sea which is destroying the marine ecosystem. In Malaysia, about 80% people are aware about the importance of recycling. However, not many people understand the concept of upcycling especially in marine park islands. Some may have misunderstood the difference between upcycling and recycling. This research focuses on what are the best and new solutions to educate islanders on the application of both upcycling and recycling at Perhentian Kecil Island. The aims of the research are to reduce solid waste in Perhentian Kecil Island and to provide a platform for people to learn the entire process turning waste into valuable products. An upcycling eco-village is proposed to improve the knowledge of upcycling and recycling. Interviews, questionnaires, observation and case studies techniques were used to collect the data. The findings were used to formulate design brief and schedule of accommodation for upcycling and recycling centre. The centre will help to reduce the issues of solid waste accumulation on the marine park islands .